THE EUROPE’S CIVIL MOVEMENTS IN GLOBALIZATION - Корнієвський, О.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The article analyzes the most notable trends in of the European society self-organization through the expansion of the new social movements and the citizen protest groups. The analysis of the contradictory position of European trade unions in defending labor, social and economic rights and interests of workers is given a prominent place. It is proved that the solution of new problems related to the socio-economic impact of the global financial and economic crisis requires new forms of socially significant self-organization in the formation of a global network of civil society.